MOLDOVAN EXTERNAL TRADE WITH EU, CIS AND OTHER COUNTRIES: ACHIEVEMENTS AND CHALLENGES - CEBAN, Alexandru (Economy and Sociology, 2021)
The foreign trade of a state represents a determinant factor in assessing its economic statute among the neighbours and in the whole world. The actuality of the studied topic is determined by the changing trade relations that the Republic of Moldova is passing through in the last years. Republic of Moldova holds the necessary criteria for becoming a competitive country in the region in terms of the manufactured and marketed goods. The aim of the study is to evaluate the foreign trade of the Republic of Moldova, by emphasizing the main traded groups of products, trade partners as well as to analyze the average price index and physical volume index of imports and exports. The paper also comes with an analysis of re-export and re-import, which represents a peculiarity for our country’s trade pattern. Research methods that have been used within the paper are the following: analogy, systemic approach, statistical and scientific analysis, Laspeyres index method. The obtained results focus on the recovery of the foreign trade between 2015 and 2017 with higher revival rates of exports, and a growing reorientation of exports towards the European Union and other countries’ markets.